Lipid perturbation compromises UPR-mediated ER homeostasis - Ng, Benjamin Si Han (2018)
Phospholipid homeostasis in biological membranes is essential to maintain cellular functions of organelles such as the endoplasmic reticulum (ER). Obesity has been associated to the perturbation of the ratio of the two most abundant phospholipids in the ER, phosphatidylcholine (PC) and phosphatidylethanolamine (PE). PC/PE disequilibrium has also been linked to metabolic diseases such as non-alcoholic fatty liver disease and type II diabetes, but its biological significance remains unclear. This study aims to develop a model of how lipid perturbation (LP) can develop into diseased states. Previously, we reported that Saccharomyces cerevisiae adapts to lipid disequilibrium by upregulating several protein quality control (PQC) pathways such as the endoplasmic reticulum-associated degradation (ERAD) pathway and the unfolded protein response (UPR). We investigated the PQC pathways at their proteomic levels to investigate their effectiveness in response to LP. Surprisingly, we observed certain ER-resident transmembrane proteins (TPs), part of the UPR programme, to be destabilised under LP. Localisation and integration of the TPs to the ER remain unaffected, suggesting that the TPs might be destabilised by changes in ER membrane composition. The ER membrane was found to have undergone fatty acid remodelling and membrane stiffening. Among these, Sbh1, a member of the translocation complex, was prematurely degraded by dissociating from the Sec61 complex. Sbh1 is targeted for degradation through its highly conserved lysine residue near the membrane in a Doa10-dependent ERAD manner. Further investigations revealed Sbh1 destabilisation could result in the translocational defect under LP. Sbh1 overexpression fails to fix the translocational defect, but ameliorate the protein processing defects found under LP. This suggests a novel role of Sbh1 in protein processing. In addition, as LP compromises the UPR, disrupting phospholipid homeostasis may be exploited to target pathogens that upregulate the UPR for survival. Two lipid genes, PfFMP and PfPSD were characterised in Plasmodium falciparum by genetic complementation in yeast. Premature removal of key ER-resident TPs under prolonged LP might be an underlying cause of chronic ER stress in metabolic disorders.